Anemia Etiology in Ethiopia: Assessment of Nutritional, Infectious Disease, and Other Risk Factors in a Population-Based Cross-Sectional Survey of Women, Men, and Children. Issue 2 (14th October 2021) - Andersen, Christopher T; Tadesse, Amare Worku; Bromage, Sabri; Fekadu, Habtamu; Hemler, Elena C; Passarelli, Simone; Spiegelman, Donna; Sudfeld, Christopher R; Worku, Alemayehu; Berhane, Yemane; Fawzi, Wafaie W
ABSTRACT: Background: While the causes of anemia at an individual level (such as certain nutritional deficiencies, infections, and genetic disorders) are well defined, there is limited understanding of the relative burden of anemia attributable to each cause within populations. Objectives: We sought to estimate the proportion of anemia cases attributable to nutrition, infectious diseases, and other risk factors among women, men, and children in 6 regions of Ethiopia. Methods: A population-based cross-sectional study was conducted. Data were obtained from 2520 women of reproductive age (15–49 y), 1044 adult men (15–49 y), and 1528 children (6–59 mo). Participants provided venous blood samples for assessment of their hemoglobin concentration; ferritin, folate, vitamin B12, and C-reactive protein levels; and the presence of malaria infection. Stool samples were collected to ascertain the helminth infection status. Sociodemographic questionnaires and a 24-h diet recall were administered. Population-weighted prevalences of anemia and risk factors were calculated. Multivariable-adjusted associations of risk factors with anemia and partial population attributable risk percentages were estimated using generalized linear models. Results: The anemia prevalences were 17% (95% CI: 13%–21%) among women, 8% (95% CI: 6%–12%) among men, and 22% (95% CI: 19%–26%) among children. Low serum ferritin contributed to 11% (95% CI: −1% to 23%) of anemia cases among women, 9% (95% CI: 0%–17%) among men, and 21% (95% CI: 4%–34%) among children. The proportions of anemia attributable to low serum folate were estimated at 25% (95% CI: 5%–41%) among women and 29% (95% CI: 11%–43%) among men. Dietary iron intake was adequate for nearly all participants, while inadequacy was common for folate and vitamin B12. Inflammation and malaria were responsible for less than 1 in 10 anemia cases. Conclusions: Folate deficiency, iron deficiency, and inflammation appear to be important contributors to anemia in Ethiopia. Folic acid food fortification, targeted iron interventions, and strategies to reduce infections may be considered as potential public health interventions to reduce anemia in Ethiopia.